2013
DOI: 10.1002/pon.3265
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of family psychosocial functioning in survivors of pediatric cancer using the PAT2.0

Abstract: Data indicate that the overall proportions of families experiencing "universal", "targeted", and "clinical" levels of familial distress may be constant from the time of diagnosis into survivorship care. Overall, the PAT2.0 demonstrated strong psychometric properties among survivors of pediatric cancer and shows promise as a psychosocial screening measure to facilitate more effective family support in survivorship care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 17 publications
(39 reference statements)
4
30
0
Order By: Relevance
“…Among child/adolescent siblings, higher distress was associated with poorer family functioning, lower parental acceptance, higher parental psychological control, and greater perceived impact of cancer on interpersonal relationships but not with parent PTSS . Multiple family risk factors conferred greater risk for sibling distress than any individual risk factors, and family risk was associated with higher likelihood of using mental health services . Mixed findings were reported for family size .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among child/adolescent siblings, higher distress was associated with poorer family functioning, lower parental acceptance, higher parental psychological control, and greater perceived impact of cancer on interpersonal relationships but not with parent PTSS . Multiple family risk factors conferred greater risk for sibling distress than any individual risk factors, and family risk was associated with higher likelihood of using mental health services . Mixed findings were reported for family size .…”
Section: Resultsmentioning
confidence: 99%
“…Studies of mental health care utilization were limited by the lack of information about siblings' untreated mental health problems, extent of missing sibling‐specific data, and exclusion of siblings with preexisting mental health problems, who are arguably at highest risk. With these limitations in mind, estimates of mental health service use ranged from 8% of adults to 15% of child/adolescent siblings of survivors, with no differences in hospital contact for mental health reasons between siblings and controls . As a proxy for mental health care utilization, antidepressant use was reported by 2% of a mixed pediatric/adult sample and 11.5% of an adult sample .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…PAT is used currently in 50 sites in the United States and has been adapted/translated for use in a number of other countries, with published reports from Canada and Australia . The PAT is also used in survivorship, with scores associated with survivors requiring psychological consultations …”
Section: Discussionmentioning
confidence: 99%
“…Families with higher risk for developing problems could be offered additional psychosocial interventions matched to their risk profile, to support optimal use of the healthcare team's resources . Previous research supported the validity of the PAT in different countries around the world and indicated that the PAT correlates with psychosocial risk and psychosocial services were provided more frequently to higher risk families . Using the PAT reduced family psychosocial risk in the first 6 months of treatment and improved quality of life related to pain in children .…”
Section: Introductionmentioning
confidence: 99%